"Everything is from God but it is always better to get to the hospital on time": A qualitative study with community members to identify factors that influence facility delivery in Gombe State, Nigeria. Issue 1 (31st December 2020) - Hill, Zelee; Scheelbeek, Pauline; Schellenberg, Joanna; Hamza, Yashua
ABSTRACT: Background: Nigeria has one of the highest maternal mortality rates in the world, but facility delivery levels are relatively low and stagnant. Few qualitative studies have explored this issue and most have focused on barriers to utilization, much can be learnt from women who already deliver in facilities. Objectives: We aimed to identify facilitators and barriers to facility delivery in Gombe State in North East Nigeria with a focus on women who have had a facility delivery. Methods: We conducted 24 narrative and in-depth interviews with mothers, and 16 focus-group-discussions with mothers, fathers, grandmothers and community health workers. Data were collected in Hausa, and transcribed and translated into English. Preliminary data analysis was conducted through team workshops, followed by systematic coding of the transcripts. Initial themes were identified a priori from the research questions and others emerged during coding. Results: A safe delivery was the main motivator for facility delivery, with facilities considered safe because of the presence of a trained health worker, the detection and management of problems, the availability of medicines and good hygiene. Those who delivered in a facility had a desire to be modern and rejected traditional practices. Decision-making power, social norms, accessibility, cost and perceived poor quality of care were reported as barriers. Community health workers, when they reached households, provided information on the benefits of facility delivery, stressed that times were changing, provided practical help such as arranging transport and, by accompanying families to the facility, brokered better quality of care and provided social support. Conclusion: This study highlights both the facilitators and barriers to facility delivery, and demonstrates the need for interventions to address a wide range of issues at multiple levels.